Synthesis, characterization and catalytic activity of Mn(III)- and Co(II)-salen complexes immobilized mesoporous alumina - Chaube, V. D.; Shylesh, S.; Singh, A. P. (Journal of Molecular Catalysis A-Chemical, 2005)
Mn(III) and Co(II)-schiff base complexes were immobilized over mesoporous alumina through the reaction of mesoporous alumina functionalized 3-aminopropyl triethoxy silane (3-APTES) and salicylic aldehyde via schiff base condensation. The surface properties of the functionalized catalysts were analyzed by a series of characterization techniques like elemental analysis, PXRD, FTIR, N(2) adsorption-desorption, TG-DTG, DR UV-vis, XPS, etc. PXRD and adsorption-desorption analysis shows that the mesostructure of alumina remains intact after various modifications, while spectral technique show the successful anchoring of the neat complexes inside the porous alumina support. The catalytic activity of the functionalized metal-salen complexes examined in the liquid phase oxidation of styrene and cyclohexene shows that the functionalized salen complexes are more active and selective than the corresponding neat metal complexes. Further, the catalyst (Mn-S-NH(2)-MA) was recycled three times in the oxidation of styrene and no major change in the conversion and selectivity is observed, which shows that the immobilized metal-salen complexes are stable under the present reaction conditions. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Immobilization; Mesoporous alumina; Oxidation; Schiff base complexes

Benzoylation of anisole over silicotungstic acid modified mesoporous alumina - Selvakumar, S.; Singh, A. P. (Catalysis Letters, 2009)
Mesoporous alumina (MA) molecular sieves were synthesized by using aluminum sec-butoxide as Al precursor and lauric acid as the structure directing agent. The synthesized MA was functionalized with silicotungstic acid (STA) via wet impregnation method and characterized by various physico-chemical techniques. The XRD patterns of a series of HPA functionalized MA are showing the ordered structures. N(2) sorption analysis shows type IV isotherm. NH(3)-TPD measurements revealed an increase in number of acid sites with an increase in loading of STA over MA. At the same time decrease in the acidity was observed with the increase in calcination temperature of the supported materials. Functionalization of STA were also carried out over different alumina supports such as catapol-B (CB) and alumina synthesized without surfactant (ASW) and their activities were evaluated by carrying out liquid phase Friedel-Craft acylation (FC) reaction of anisole with p-toluoyl chloride in a batch reactor at 120 degrees C. Recycling was performed in the FC reaction using 30 wt% STA-MA two times and no major deactivation of the catalyst was observed.
Keywords: Friedel-Craft acylation; Mesoporous alumina; Silicotungstic acid

Promoted mesoporous Fe-alumina catalysts for the non-oxidative dehydrogenation of isobutane - Venugopalan, Aswathy Thareparambil; Kandasamy, Prabu; Gupta, Nikitra Nihalchand; Thirumalaiswamy, Raja (Catalysis Communications, 2021)
Production of isobutene is commercially consequential and highly demanding from the end-use industries being a key platform molecule as well as an intermediate for a variety of value-added chemicals. Traditionally, isobutene is prepared via steam cracking and fluid catalytic cracking methods. However, the catalysts used in these conventional methods have disadvantages like coke formation, sintering, etc. In this study, the catalytic non-oxidative dehydrogenation of isobutane over acidic, alkaline, and noble metal promoted mesoporous iron-doped catalysts was investigated. Iron doping has a significant function in controlling isobutene selectivity. The synthesis method is crucial to achieve successful metal doping in the mesoporous alumina matrix. Promoted catalysts exhibited a notable difference in isobutane conversion with a marginal change in dehydrogenation selectivity. Silver promoted catalyst showed slightly higher isobutene yield due to the optimal catalytic properties. This catalyst was stable for a considerable duration, and coke deposition, as well as particle agglomeration, were observed to faintly inhibit the catalytic activity.
Keywords: iron; Isobutane; Isobutene; Mesoporous alumina; Non-oxidative dehydrogenation